2016
DOI: 10.1002/jor.23248
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic and mixed cancer metastasis modulates collagen and mineral parameters within rat vertebral bone matrix

Abstract: Metastatic involvement in vertebral bone diminishes the mechanical integrity of the spine; however minimal data exist on the potential impact of metastases on the intrinsic material characteristics of the bone matrix. Thirty-four (34) female athymic rats were inoculated with HeLa (N = 17) or Ace-1 (N = 17) cancer cells lines producing osteolytic or mixed (osteolytic and osteoblastic) metastases, respectively. A maximum of 21 days was allowed between inoculation and rat sacrifice for vertebrae extraction. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…This is further motivated as while studies have shown a negative relationship between pen concentration and bone strength, other works have found a negative, positive, or no relationship between bone stiffness and pen concentration. The observed increase in pen levels and decrease in dpyr levels in the osteolytic vertebral bone seen in previous work may be indicative of diminished vertebral mechanical behavior independent of its compromised architecture.…”
Section: Discussionsupporting
confidence: 51%
“…This is further motivated as while studies have shown a negative relationship between pen concentration and bone strength, other works have found a negative, positive, or no relationship between bone stiffness and pen concentration. The observed increase in pen levels and decrease in dpyr levels in the osteolytic vertebral bone seen in previous work may be indicative of diminished vertebral mechanical behavior independent of its compromised architecture.…”
Section: Discussionsupporting
confidence: 51%
“… 21 , 23 , 25 , 26 The mineral component is often calcium-deficient, and possesses carbonate substitutions with respect to stoichiometric hydroxyapatite. Recent investigations have extended the assessments of bone fragility and metastatic lesions using Raman spectroscopy to include in-depth evaluations of collagen integrity 16 , 18 , 24 along with the contributions of proteoglycans, tissue water, and lipids 17 as well as oxidative damage. 39 …”
Section: Resultsmentioning
confidence: 99%
“…The degree of bone remodeling was estimated as the carbonate ν 1 /amide I ratio (since the carbonate-to-matrix ratio has been associated with increased risk of fracture), and mineral crystallinity as the reciprocal of full-width at half maximum (FWHM) of phosphate ν 1 peak. 16 , 21 , 23 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations